2013
DOI: 10.1097/nna.0b013e318283dc02
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Bedside Shift Report to Improve the Effectiveness of Shift Handoff

Abstract: Handoff of patient information during shift report between nurses is a time of risk and liability. A quality improvement project was conducted on a 23-bed inpatient unit to measure the value of a bedside change-of-shift report in improving the effectiveness of shift report. Indicators including end-of-shift overtime, call light usage, nurse perceptions, and patient satisfaction were impacted by the change in process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 15 publications
1
81
0
3
Order By: Relevance
“…Regardless of the report method, the literature is consistent regarding the problems associated with change-of-shift report. The problems include a lack of report consistency and structure, potential failures in communication leading to adverse events, and not allowing the patient to be included in their plan of care (Cairns, Dudjak, Hoffmann, & Lorenz, 2013;Friesen et al, 2013;Jeffs et al, 2014). Much of the literature has found that many medical errors involve actual inaccuracies with communication.…”
Section: Traditional Versus Non Traditional Nursing Reportmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of the report method, the literature is consistent regarding the problems associated with change-of-shift report. The problems include a lack of report consistency and structure, potential failures in communication leading to adverse events, and not allowing the patient to be included in their plan of care (Cairns, Dudjak, Hoffmann, & Lorenz, 2013;Friesen et al, 2013;Jeffs et al, 2014). Much of the literature has found that many medical errors involve actual inaccuracies with communication.…”
Section: Traditional Versus Non Traditional Nursing Reportmentioning
confidence: 99%
“…A study by Cairns et al (2013), found a decrease in end-of-shift overtime by 10 minutes per day, or 61 hours per year, demonstrating an overall savings in overtime by 23%. Street et al, 2013 stated "frequent interruptions" as barriers to bedside reporting (p.139).…”
Section: Barriers Of Bedside Reportingmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper handoffs may be reliant on the communication skill-level of the nurses providing the information. Cairns, Hoffmann, Dudjak, and Lorenz (2013) suggest "an experienced nurse may provide more in-depth information or may conversely assume a baseline of knowledge among peers that may not be present" (p. 160). Shift report that occurs away from the bedside can lack structure and become lengthy, BSR allows for the patient to add insight and ask questions.…”
Section: Bedside Shift Reportmentioning
confidence: 99%